’Pant Urd-31’: a leading variety of blackgram - Singh, D. P. (Indian Farming, 2018)
‘Pant Urd 31’ was released as first variety of blackgram. It has combination of desirable traits (dwarf, early maturity, photo-thermoinsensitivity and resistance to foliar diseases). Its breeder seed production has increased from 6.75 to 20.05% of the total breeder seed produced of all the varieties of blackgram. To achieve additional income to the farmer its introduction is required.